2006
DOI: 10.1103/physrevb.73.155317
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-controlled hole spin injection in nonmagneticGaAsAlAsresonant tunneling structures

Abstract: We have investigated polarization-resolved photoluminescence under applied voltage in p-i-p GaAs/ AlAs double-barrier diodes. We have observed oscillations in the degree of polarization up to 36% at B = 15 T with sign reversals occurring near to the hole subband resonances. At high voltages a polarization saturation up to 25% at B = 15 T is observed. The data are interpreted by using simulations based on a simple theoretical model that considers spin conservation for tunneling and the relaxation processes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…This indicates that a significant charge build-up must occur in the GaAs QWs [13] of the biased RTDs. The excitonic spin-splitting of the QW emission bands from the S0 structure are almost zero (~1 meV for the GaAs and ~0 meV for the InGaAs QW) in agreement with previous results [9]. However, we observe a small increase of the spin-splitting energies for the S1 structure for both QWs (~ 2 meV for the GaAs and ~1 meV for the InGaAs QW) as compared to the S0…”
supporting
confidence: 64%
See 1 more Smart Citation
“…This indicates that a significant charge build-up must occur in the GaAs QWs [13] of the biased RTDs. The excitonic spin-splitting of the QW emission bands from the S0 structure are almost zero (~1 meV for the GaAs and ~0 meV for the InGaAs QW) in agreement with previous results [9]. However, we observe a small increase of the spin-splitting energies for the S1 structure for both QWs (~ 2 meV for the GaAs and ~1 meV for the InGaAs QW) as compared to the S0…”
supporting
confidence: 64%
“…Since hole spin relaxation times are much shorter than electron spin relaxation times, the improvement of spin injection efficiency in those structures is a difficult issue. In the last years, it was also shown that spin-polarization of holes in p-i-p Resonant Tunneling Diodes (RTDs) can be voltage-selected, which makes such device attractive for spintronic applications [9][10][11][12]. A possible improvement of spin-LEDs could thus be obtained by using the resonant tunneling effect in association of a layer of GaMnAs acting as a spin injector in p-i-n RTDs.…”
mentioning
confidence: 99%
“…For example, it was shown that spin polarization of carriers in RTDs can be voltage and light dependent under magnetic field [8][9][10] . Strong oscillations of circular polarization degree (CPD) were observed in RTDs under applied bias and high magnetic fields with maximum values around the resonant peak voltages 8 . In addition, it was evidenced the formation of highly spin-polarized two dimensional (2D) 3 gases under high magnetic fields which are responsible for spin polarized injection of carriers into the quantum well (QW) of the RTDs 11 .The formation of excitonic complexes in RTDs at hole and electron resonant tunneling condition was also demonstrated 12,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Resonant tunneling diodes (RTDs) have also been a research focus for many years [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Several works investigated their fundamental physical properties and possible potential applications in spintronics [8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation